Taming the Shock: EU Education of Ukrainian Refugees through the Lesson of Ian Hacking - Daniel Boccacci (Formazione & Insegnamento, 2023)
The tragic event of the war in Ukraine has prompted the EU to promote welfare-type educational policies, such as those expressed in the Cohesion's Actions for Refugees (CARE), and to rely on a large amount of statistical data. The category of the Ukrainian refugee, developed through this type of knowledge, is framed in the article as an expression of a positivistic-inferential process. This is prominent in industrial societies and is interpreted through the key concepts of «probability» and «normal state», explored in The Taming of Chance (1990) by Ian Hacking. The history of the present, that emerges from these analytical concepts, can help to relativize the evidence of contemporary international policy making. This allows us to reflect on the ongoing normalization towards the Ukrainian refugee. The educational action is deprived of the relational generative potential to be caged within the dichotomy between the needy refugee student and the Western actors who “save”.